Cardiovascular effects of prenalterol on rest and exercise haemodynamics in patients with chronic congestive cardiac failure. Issue 4 (April 1982) - Tweddel, A C; Murray, R G; Pearson, D; Martin, W; Hutton, I
Abstract : ?The cardiovascular effects of the cardioselective beta, agonist prenalterol have been studied in nine patients with severe chronic congestive cardiac failure and in six patients with left ventricular dysfunction resulting from previous myocardial infarction. In the patients with cardiac failure intravenous prenalterol in a dosage of 1.5 microgram/kg bodyweight increased the cardiac index from 1.8 +/- 0.1 to 21.+/- 0.1 1/min per m2 and the left ventricular ejection fraction from 22 +/- 3 to 28 +/- 3%. There was a modest but significant increase in heart rate from 76 +/- 3 to 87 +/- 4 beats/min. Systemic vascular resistance fell from 2285 +/- 51 to 2041 +/- 534 dynes s-1 cm-5. On exercise, the left ventricular filling pressure fell from 33 +/- 6 to 26 +/- 3 and both cardiac index and stroke index increased by 13% and 16%, respectively. There was no significant change in heart rate or systemic blood pressure. In the patients with left ventricular dysfunction, coronary sinus blood flow increased from 107 +/- 11 to 133 +/- 12 ml/min but the increase in myocardial oxygen consumption was small and not significant (11.6 +/- 1.2 and 14.5 +/- 1.9 ml/min). In all patients there was no evidence that prenalterol was arrhythmogenic.